KORELASI PENGALAMAN MENGAJAR, PELATIHAN, DAN MOTIVASI BERPRESTASI DENGAN KOMPETENSI PROFESIONAL GURU SEKOLAH DASAR PONTIANAK BARAT - Mutmainnah Mutmainnah; Muhammad Asrori; Hairida Hairida (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
ABSTRACTThis study aims to describe the correlation between teaching experience,training, and achievement motivation with the professional competence ofteachers in West Pontianak Barat Elementary Schools. This study used aquantitative approach, descriptive methods with correlation research type.Data collection was carried out using a questionnaire. The data analysistechnique was carried out by using descriptive statistical analysis and todetermine the relationship between teaching experience, training, andachievement motivation with the professional competence of teachers usingsimple correlation analysis and multiple correlation. The results of the studyconcluded that there was a positive and significant relationship between: ( 1)teaching experience with teacher professional competence (r1y= 0.721), (2)training with teacher professional competence (r2y= 0.591), (3) achievementmotivation with teacher professional competence (r3y= 0.674), (4) experienceteaching and training with teacher professional competence (Ry-12= 0.733), (5)training and achievement motivation with teacher professional competence (Ry-23= 0.674), (6) teaching experience and achievement motivation with teacherprofessional competence (Ry-13= 0.759), (7) teaching experience, training, andachievement motivation with the professional competence of teachers (Ry-13=0.762) with a combined contribution The variable teaching experience,training, and achievement motivation on the professional competence ofteachers is 58%.Keywords: Teaching Experience, Training, Achievement Motivation andTeacher Professional Competence.